Neoadjuvant Chemo-Endocrine Therapy for Hormone Receptor Positive Breast Cancer: A Meta-Analysis - Zhen-Yu Li; Ying-Li Dong; Xiao-Zhong Cao; Sha-Sha Ren; Zhen Zhang (Clinical and Experimental Obstetrics & Gynecology)
Background: Neoadjuvant chemotherapy has become the standard treatment for patients with locally advanced breast cancer. However, patients with hormone receptor positive (especially human epidermal growth receptor 2 negative) breast cancer show low response rate to neoadjuvant chemotherapy. Whether neoadjuvant chemo-endocrine therapy (NCET) can improve the pathological complete response (pCR) rate of these patients remains controversial. Methods: A systematic literature search was conducted in the PubMed, Embase, and Cochrane databases. Pooled odds ratio (OR) with 95% confidence intervals (CI) was calculated. Results: Five randomized controlled trials were included (N = 566). NCET did not significantly improve pCR (OR 1.35, 95% CI 0.77–2.38, p = 0.30). Conclusions: NCET did not to improve the pCR rates in patients with hormone receptor positive breast cancer.